Phylogenomics of Tanypodinae (Diptera: Chironomidae) redefines relationships in Procladiini and Tanypodini and supports a new tribe - Xiu-Ru Xiao; Yi-Ni Zhang; Hai-Feng Xu; Zhi-Chao Zhang; Yu-Yi Jiang; Yan-Xin Chen; Chen-Hong Li; Bing-Jiao Sun; Fabio Laurindo da Silva; Xiao-Long Lin (Molecular Phylogenetics and Evolution, 2026)

A salivary elicitor MsPDI3 from Mythimna separata triggers plant defense responses - Jin-Da Wang; Huan-Tai Lin; Lin Li; Yao-Hui Chen; Ran Wang; Honglin Feng; San-Ji Gao (Insect Biochemistry and Molecular Biology, 2026)

Exciton regulation and directional electron transfer in artemisia-derived carbon dots/g-C3N4 heterojunction for enhanced visible-light photocatalytic antibacterial activity - Mingzhu Yuan; Weile Xie; Ran Qiu; Mingxin Zhou; Yangyang Li; Yuanxu Liu; Zibing Liu; Yupeng Yuan; Da Fu; Xiangang Lin (Chemical Engineering Journal, 2026)

Caged xanthones with cytotoxic activity from the leaves and twigs of Garcinia oligantha - Xiao-Hui Peng; Sha Chen; Si-Yu Wang; Jin-Yuan Yang; Hao-Nan Li; Bin Lin; Hui-Ming Hua; Da-Hong Li (Phytochemistry, 2026)

Enhanced simultaneous nitrogen and phosphorus removal via a step-feed anoxic/oxic process coupled with side-stream enhanced biological phosphorus removal - Ruoyu Wu; Dongqi Wang; Mengbo Huang; Yanzhe Gong; Guangxiang Duan; Jiayu Bi; Wengui Gu; Lu Qin; Yuan Guo; Xiaopeng Qiu; Yishan Lin; Da Kang; et al. (Journal of Environmental Chemical Engineering, 2026)

Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Spatiotemporal radical engineering via non-destructive synchrotron lithography for multimodal functionalization of inert polymers - Hao Zhang; Xincheng Xie; Shengbin Cao; Fan Zhang; Lin Da; Yang Liu; Bomin Liu; Feng Tian; Caizhen Zhu; Xiuhong Li; Jian Xu (Chemical Engineering Journal, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Isolation, structural elucidation, and activities evaluation of proaporphine alkaloids from Thalictrum baicalense - Meng-Yue Yang; Jing-Jing Xue; Zhao-Jing Chen; Xiao-Peng Guo; Shi-Meng Qin; Han-Gao Yang; Fang-Shen Liu; Zhan-Lin Li; Da-Hong Li; Ya-Ting Sun; Hui-Ming Hua (Phytochemistry, 2026)

Atomically precise ferrocene-based Fe/Mn nanocluster for solar-driven cycloaddition of epoxides with carbon dioxide - Xue-Feng He; Chun-Yang Li; Yu-Lin Jiang; Wan-Yu Zhu; Qiu-Hong Cheng; Kun Huang; Da-Bin Qin; Xiang-Yu Zhang (Chemical Engineering Journal, 2026)

The undescribed alkaloids from Jacobaea cannabifolia (less.) E. Wiebe and their anti-inflammatory activities - Jian-Zhe Li; Juan Pan; Yu Bi; Zhi-Chao Hao; Wei Guan; Hai-Xue Kuang; Qing-Shan Chen; Li-Li Zhang; Xin-Yue Wu; Da-Lin Li; Bing-You Yang; Yan Liu (Natural Product Research, 2026)

Corrigendum to Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae. Journal of Environmental Sciences (2026), doi: https://doi.org/10.1016/j.jes.2026.03.02 - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Ultrasound-driven structural and functional modifications of grape seed protein revealed by power- and duration-dependent experiments - Ying-Yang Liu; Da-Rui Tang; Shi-Ling Wang; Wei-Wei Li; Jun-Wei Xu; Lian-Bing Lin; Yu-Hang Jiang; Qi-Lin Zhang (Food Hydrocolloids, 2026)

Pollutant-specific pathways linking gaseous air pollution to adolescent depressive symptoms: Direct and sleep-mediated effects in a population-based retrospective cohort study - Chun-Ji Lin; Po-Ya Chang; Yu-Ling Li; Chih-Da Wu; Chao-Ying Tu; Chih-Yi Wu; Szu-Ying Chen; Hung-Yi Chiou (Environmental Research, 2026)

Differential light spectrum regulation of oogenesis and spermatogenesis in Plectropomus leopardus - Hui Ding; Lin Li; Da Zheng; Mingjian Liu; Jinyang Xie; Binglin Li; Yuli Li; Zhenmin Bao; Bo Wang; Jingjie Hu (Aquaculture, 2026)

Mechanistic responses of coccolithophores to exposure to the marine pollutant atrazine - Xiang-Wu Chen; Yi-Tong Huang; Yue-Tao Song; Zhuo-Fan Li; Xue-Ling Huang; Da-Wei Li; Lin-Jian Ou (Water Research, 2026)

Simultaneous removal of organic and inorganic arsenic: A critical evaluation of direct adsorption and hybrid catalytic oxidation-adsorption pathways - Huiping Zeng; Guoyang Ma; Xiaoying Zheng; Da Lin; Jie Zhang; Dong Li (Chemical Engineering Journal, 2026)

Aged nanoplastics exacerbate CPPD-induced ocular toxicity via the thyroxine pathway in zebrafish - Jin Li; Yi Zheng; Yuying Yin; Wenda Gao; Fan Tang; Xinlin Zhao; Qi Xin; Suiyi Liu; Jiaqi Xiong; Jian Lin; Da Sun; Jiangfei Chen (Aquatic Toxicology, 2026)

Viral communities as mirrors and vectors: Tracing antibiotic resistome distribution and dissemination across diverse habitats in Macao - Yu-Qiu Ye; Da Lin; Luo-Qin Shen; Di Wu; Ying Li; Yi-Fei Wang; Dong Zhu (Journal of Hazardous Materials, 2026)

Lithium isotope fractionation in LCT pegmatite systems: a density functional theory study - He-Feng Lin; Wen-Bin Zhu; Hai-Zhen Wei; Xi-Sheng Xu; Zhi-Qin Xu; M.R. Palmer; Shuang Chen; Jing Ma; Yin-Chuan Li; Da-Sheng Zuo; Ke Yang (Geochimica et Cosmochimica Acta, 2026)

Three-Dimensional Fast Marching Seismic Traveltime Computation Based on Coarse-Grid Interpolation - Yan-song Li; Jun-jie Yang; Xue-feng Gao; Hui Sun; Yun Long; Peng Lin; Song-da Ji; Hong-yong Ren; Rui Chen (Applied Geophysics, 2026)

Comprehensive understanding of new particle formation in China through advanced modeling - Jiewen Shen; Bin Zhao; An Ning; Wei Nie; Chao Yan; Yuyang Li; Runlong Cai; Alfonso Saiz-Lopez; Manish Shrivastava; Biwu Chu; Da Gao; Nanna Myllys; et al. (Science Bulletin, 2026)

Structurally diverse sesquiterpenoids from the fruits of Magnolia grandiflora Linn. and their cytotoxic activities - Qiu-Ye Zhao; Jin-Da Li; Shi-Huan Yin; Zhen-Quan Li; Hui-Ling Zhou; Jia-Qing Feng; Wei-Yang Feng; Xing-De Wu; Lin-Fen Ding (Phytochemistry, 2026)

Predatory performances and adaptive strategies of Eocanthecona furcellata (Hemiptera: Pentatomidae) to the larvae of Phauda flammans (Lepidoptera: Phaudidae) - Jian-Zhong Ning; Da-Xing Lu; Xiong Zhao He; Xiao-Yun Wang; Kai Lin; Jun Li; Xia-Lin Zheng (Applied Animal Behaviour Science, 2026)

Integrated basin-scale assessment of legacy and emerging PFAS in the Xiangjiang River Basin, China: Occurrence, source apportionment, and risk prioritization - Da-Ying Lin; Li-Xin Hu; You-Sheng Liu; Jin-Na Zhang; Guang-Guo Ying (Water Research, 2026)

Construction of a coccolithophore database platform for ecological and molecular applications - Xue-Ling Huang; Yi-Xin Xiong; Shuang Yu; Xiang-Wu Chen; Da-Wei Li; Lin-Jian Ou (Water Research, 2026)

In-situ reactivation of the catalyst for hydrodeoxygenation of bio-oil to biofuel by coupling the self-rotation and revolution of catalysts in the swirling flow - Yao Zhang; Zheng-hao Yang; Yu-long Chang; Jian-ping Li; Bang-da Wang; Zi-heng Jin; Liang Ma; Xia Jiang; Hua-lin Wang (Journal of Cleaner Production, 2026)

Prenatal and postpartum residential greenness and behavioral development in early Childhood: Findings from a birth cohort - Wen-Chi Chao; Ming-Lun Zou; Chih-Da Wu; Jian-Pei Huang; Heng-Kien Au; Chen-Li Lin; Shih-Peng Mao; Hsing-Jasmine Chao; Ling-Chu Chien; Hsueh-Wen Hsu; Pilyoung Kim; Yi-Hua Chen (Environmental Research, 2026)

High-performance composite solid electrolyte with elevated ionic liquid and high-dielectric high-entropy oxide in poly(vinylidene fluoride-co-hexafluoropropylene) for advanced lithium-ion batteries - Wen-Hsuan Lu; Yen-Shuo Huang; Yen-Lin Chen; Yi-Hsuan Tseng; Jue-Hua Pan; You-Yi Li; Ying-Da Luo; Chun-Han Kuo; Chih-Ping Tan; Ruey-An Doong; Ho-Hsiu Chou; Ai-Yin Wang; et al. (Chemical Engineering Journal, 2026)

A novel endophytic Kineococcus from rice against Fusarium culmorum and Fusarium sporotrichioides and whole-genome analysis - Yayun Liu; Lin Liu; Zhuanxia Lei; Ruping Zhang; Lin Zhao; Fenglan Li; Da Zhang; Qingyue Yu (Antonie van Leeuwenhoek, 2026)

Zedoarondiol inhibits monocyte adhesion and expression of VCAM and ICAM in endothelial cells induced by oxidative stress - Bei-li Xie; Yu-long Bie; Bo-ce Song; Ming-wang Liu; Lin Yang; Jiangang Liu; Da-Zhuo Shi; Fu-Hai Zhao (Natural Product Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

An enhanced sorting method for second-life lithium-ion batteries based on two-step clustering - Fu Wan; Yupeng Lin; Da Yang; Shufan Li; Ruiqi Liu; Lei Zhu; Wenwei Yin; Weigen Chen (Journal of Cleaner Production, 2026)

NeuProIO: A dual-action solid drug nanoparticle topical formulation for simultaneous intraocular pressure reduction and neuroprotection for glaucoma - Lei Xu; Mu Li; Lin Qi; Tzu-Chen Wang; Dong Liu; Vimalin Jeyalatha Mani; Hsin-Yin Chuang; Qingbo Yang; Ruipu Mu; Samira Mahdi; Da Huang; Honglan Shi; et al. (Chemical Engineering Journal, 2026)

EED226 treatment targets key immune genes to suppress LPS response in Chinese tongue sole splenocytes - Yangqing Zhang; Lei Lin; Duan Liao; Shengyu Zhu; Yanan Li; Lucas Benites Doretto; Ivana Felipe da Rosa; Yajun Wang; Hong-Yan Wang; Changwei Shao (Fish & Shellfish Immunology, 2026)

Enhancing capacitive energy storage in Na0.5Bi0.5TiO3-based relaxor ferroelectric ceramics by tuning polymorphic polar nanoregions - Binglong Zheng; Ying Lin; Fei Yan; Qibin Yuan; Yongzhen Ma; Yanlong Ma; Yu Zhang; Da Li; Haibo Yang (Chemical Engineering Journal, 2026)

Applying Interpretable Machine Learning for Hypoxia Mitigation: an Operational Framework Coupling Predictive Modeling and Causal Inference for Urban River Management - Jia-yun Chen; Da-wei Wang; Zu-lin Hua; Ke-jian Chu; Li Gu (Water Resources Management, 2026)

Screening and In Vivo Validation of Key Genes Involved in Myelin Damage in Alzheimer’s Disease - Hai-Tao Li; Ji-Wei Zhang; Bo-Wen Li; Hong-Yun Wu; Jin-Wen Ge; Da-Hua Wu; Quan-Lin Zhao; Ya-Han Wang (Molecular Neurobiology, 2026)

The Combination of Sodium Tanshinone IIA Sulfonate and Mesenchymal Stem Cell-derived Exosomes Against Spinal Cord Injury via VEGF Pathway - Dan Luo; Lin Ma; Zhijian Pan; Ling Chen; Zhifeng Hu; Chaolun Liang; Zenglu Wang; Zhifeng Xiao; Dingkun Lin; Jinfeng Li; Da Guo; Xing Li (Molecular Neurobiology, 2026)

Microbial drivers of N₂O mitigation in soils: Role of nosZ II subclades under conservation tillage and stover mulching - Da-Cheng Hao; Yaoxuan Wang; Yuanyuan Luan; Fangbo Deng; Hongtu Xie; Yongxin Lin; Xuanqi Li; Zhongjun Jia; Lianfeng Wang (Applied Soil Ecology, 2026)

CHI–GSE–Nano-ZnO coating delays grape postharvest deterioration by inhibiting excess ROS via MYB714-pSTS484-mediated resveratrol biosynthesis - Yun-Lu Song; Jia-Lin Xing; Charles Ampomah-Dwamena; Shuai-Hui Ma; Mao-Song Pei; Han-Li Liu; Rui-Ping Feng; Yong-Ke Wu; Tong-Lu Wei; Hai-Nan Liu; Da-Long Guo (Food Bioscience, 2025)

Voltage-Gated sodium channel Nav1.6 mediates glioblastoma proliferation and migration via Na+/H+ Exchanger-1 and inhibits apoptosis through ERK-AKT pathway - Samed Ahmed Alezzi Alameri; Yue Kong; Qing-Da Shi; Yue-Lin Huang; Ao-Ran Sui; Dan-Dan Zhu; Ying-Zi Wang; Wang Miao; Shao Li; Guang Yang (Molecular Biology Reports, 2025)

Microplastics modulate neutrophil migration via an ROShistone lactylation positive feedback loop - Yi-li Wang; Xiao-chen Yuan; Chun-jiao Wei; Ke-yun Li; Lin-xi Zuo; Hao-yi Zhang; Rui-chen Ding; Ren Zhou; Yun-hua Zhang; Da-long Ren (Journal of Hazardous Materials, 2025)

Separation and recovery of vanadium from leaching solution of calcium roasting vanadium slag by extraction with P204 extractant - Da-long Wang; Lin Zhang; Jing-wei Li; Chen Chen; Yin-he Lin; Zhi Yang; Da-ya Wang; Huan-jian Hou; Jian Chen; Tang-jie Zhou; Wen-ming Tang (Minerals Engineering, 2025)

Separation and recovery of iron from vanadium extraction tailing slag by P204-P507 mixture collector flotation process - Yi-bo Wang; Jing-wei Li; Xiao-long Liu; Xin-fei Jiang; Yin-he Lin; Zhi Tian; Jun-jie Yin; Bing-qing Huang; Jia-xin Yang; Chen-xuan Wang; Zi-wang Wu; Shi-xing Ma; et al. (Journal of Environmental Chemical Engineering, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Vanadium-cobalt oxide nanoflower catalyst for efficient and stable overall water splitting in alkaline and seawater electrolytes - Yong-qi Tian; Song-lin Xu; Jia Li; Shuang-shuang Zhang; Bo-yao Zhang; Rong-da Zhao; Fu-fa Wu; De-peng Zhao (Next Research, 2025)

Synthesis of magnetic zeolite from iron sludge and fly ash for simultaneous nitrogen and phosphorus removal - Huiping Zeng; Simin Li; Jiongru Liang; Zhanguo Li; Da Lin; Jie Zhang; Dong Li (Journal of Water Process Engineering, 2025)

Metabolomic profiling unveils biochemical dynamics in spontaneously fermented grape leaf by-products: towards sustainable agricultural waste valorization - Jia-Lin Xing; Yun-Lu Song; Yan-Ge Li; Lu Yang; Ke-Ying Duan; Ding-Ding Zuo; Jing Zhang; Hai-Nan Liu; Tong-Lu Wei; Mao-Song Pei; Da-Long Guo (Food Bioscience, 2025)

Warming exacerbates the effects of pesticides on the soil collembolan gut microbiome and antibiotic resistome - Ya-Ning Wang; Tian-Gui Cai; Ying Li; Wen-Cai Dai; Da Lin; Jin-Ting Zheng; Yi-Fei Wang; Dong Zhu (Journal of Hazardous Materials, 2025)

Integrating synergistic effects of biodiversity conservation and ecosystem services into nature conservation strategies - Luu Van Thong Trac; Da-Li Lin; Chen-Fa Wu (Journal of Environmental Management, 2025)

Current status and research progress of sugarcane stem borers management - Jin-Da Wang; Huan-Tai Lin; Xian-Kun Shang; Hong-Li Shan; Ji-Hu Li; Xue-Hong Pan; Jiong Yin; Cheng-Wu Zou; Bao-Shan Chen; San-Ji Gao (European Journal of Agronomy, 2025)

All-in-one and on-demand wound dressing based on a deep eutectic solvent ionic gel - Jia-Yu Yang; Yu-Lin Tsai; Ting-Hui Cheng; Yu-Lin Su; Yi-Kai Hong; Yu-Chen Lin; Da-Huei Lee; Chao-Chun Yang; Chao-Kai Hsu; Li-Chieh Kuo; Cheng-Hsin Chuang (Chemical Engineering Journal, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Uptake, translocation, and biotransformation of phthalate acid esters in crop plants: A comprehensive review - Nai-Xian Feng; Bogui Pan; Hong-Jia Huang; Yi-Tong Huang; Hui Lyu; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Da-Wei Li; Ce-Hui Mo (Journal of Hazardous Materials, 2025)

Geochemistry, geochronology and Fe-Mg-S isotopic composition of the Liaoshang gold deposit, Jiaodong Peninsula, China: Implications for ore-forming processes and mineral exploration - Yuan-lin Chen; Huan Li; Shang-yi Gu; Scott A. Whattam; Chao-yang Zheng; Li-gong Wang; Da-dou Li; Liu-an Duan (Journal of Geochemical Exploration, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Boosting catalytic performance of N doped porous carbon derived from coal tar pitch: The role of N species and the contribution of 1O2 - Linlin Huang; Xuwen Zhang; Lin Wang; Tingting Liu; Da Li; Tao Sheng; Caiyu Sun; Lixin Li (Journal of Water Process Engineering, 2025)

A formula of quantile of extreme wind pressure coefficient to estimate wind load with various mean recurrence intervals - Lin Da; Qingshan Yang; Min Liu; Ke Zhou; Chuang Li (Engineering Structures, 2025)

Boosting photocatalytic hydrogen evolution from binary mixture of hydrophilic-hydrophobic conjugated polymer dots with variable saponification degrees and molecular weights - Khanh Do Gia Huynh; Yu-Ting Huang; Meng-Che Tsai; Islam M.A. Mekhemer; Jayachandran Jayakumar; Yu-Tung Lin; Chun-Hao Li; Swatilekha Pratihar; Tse-Fu Huang; Dung Chau Kim Hoang; Shang-Da Yang; Ho-Hsiu Chou; et al. (Chemical Engineering Journal, 2025)

Association between sleep quality and serum biomarkers among long-term hot spring bathers: a cross-sectional study - Fen Yang; Yue Zou; Ying-ying Zhang; Hong-xia Li; Yi-hang Xu; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Yuan Yuan; Yun Zhou; Da-yong Zeng; et al. (International Journal of Biometeorology, 2025)

Histological and transcriptome analysis of gonadal development provides new insights into the characteristics of sex differentiation and the screening of key genes in the golden pompano (Trachinotus blochii) - Feibiao Song; Huan Liang; Zhi Li; Da Zheng; Huapeng Chen; Xinxin Wang; Chaoyue Deng; Wenyan Lin; Changlin Chen; Junlong Sun; Li Zhou; Jian Luo (Aquaculture, 2025)

Unveiling airborne threats: Vertical profiles of multiple emerging pollutants in PM2.5 across the urban atmosphere of Southern China - Shu-Qing Qiu; Yan-Jun Tang; Li-Xin Hu; Cheng-Lei Pei; Da-Chi Hong; Da-Ying Lin; Geng Kang; Sheng-Zhen Zhou; Bao-Ling Liang; She-Jun Chen; Hong Bai; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Curculigoside Regulates Apoptosis and Oxidative Stress Against Spinal Cord Injury by Modulating the Nrf-2/NQO-1 Signaling Pathway In Vitro and In Vivo - Yu Hou; Chaolun Liang; Lili Sui; Yang Li; Kai Wang; Xing Li; Kunrui Zheng; Haitao Su; Dianweng Xie; Dingkun Lin; Da Guo; Le Wang (Molecular Neurobiology, 2025)

Trimeric tetrapeptide repeat protein TPR16 positively regulates salt stress in apple - Qing Wang; Da-Ru Wang; Xin Liu; Guo-Lin Chen; He-Dan Li; Wen-Long Ji; Man-Shu Qu; Rui Yang; Chun-Xiang You (Journal of Plant Physiology, 2025)

Gelation properties and swallowing characteristics of heat-induced whey protein isolate/chia seed gum composite gels as dysphagia food - Lin Li; Yu-Qiao Wang; Lin-Da Zhang; Jia-Nan Yan; Ce Wang; Bin Lai; Hai-Tao Wu (Food Chemistry, 2025)

Enhancing indoor air quality and cardiopulmonary health in patients with asthma by photocatalytic oxidation and filters air cleaner - Jia Lin Zhang; Guan-Yu Liao; Hong-Yi Lin; Jie-An Xie; Wan-Chen Li; Huang-Chi Chen; Da Wei Wu; Huai-Lei Juan; Jia-Yu Kuo; Pei-Shih Chen (Journal of Hazardous Materials, 2025)

The change rule of lipid oxidation and hydrolysis driven via water in Antarctic krill oil: Based on association colloid formation - Xue-Chen Pei; Xiang-Bo Zeng; De-Yang Li; Xin-Miao Wang; Fa-Wen Yin; Hui-Lin Liu; Da-Yong Zhou (Food Chemistry, 2025)

Three-dimensional Heterogeneity and Intrinsic Plasticity of the Projection from the Cerebellar Interposed Nucleus to the Ventral Tegmental Area - Chen Wang; Si-Yu Wang; Kuang-Yi Ma; Zhao-Xiang Wang; Fang-Xiao Xu; Zhi-Ying Wu; Yan Gu; Wei Chen; Ying Shen; Li-Da Su; Lin Zhou (Neuroscience Bulletin, 2025)

Associations of maternal serum concentration of iron-related indicators with gestational diabetes mellitus in Chinese: A pilot prospective cohort study - Geng-dong Chen; Peng-sheng Li; Zi-xing Zhou; Ting-ting Pang; Hai-yan Wang; Xiao-yan Gou; Shao-xin Ye; Dong-xin Lin; Da-zhi Fan; Zheng-ping Liu (Journal of Trace Elements in Medicine and Biology, 2024)

Insights into the accumulation and hepatobiliary transport of bisphenols (BPs) in liver and bile - Jie Ding; Ying Liu; Yanjie Li; Yongheng Huang; Shibo Li; Fei Wang; Da Chen; Bin Lu; Nan Lin (Environmental Research, 2024)

Transplantation of Wnt5a-modified Bone Marrow Mesenchymal Stem Cells Promotes Recovery After Spinal Cord Injury via the PI3K/AKT Pathway - Haimei Yang; Chaolun Liang; Junhua Luo; Xiuzhen Liu; Wanshun Wang; Kunrui Zheng; Dan Luo; Yu Hou; Da Guo; Dingkun Lin; Xiasheng Zheng; Xing Li (Molecular Neurobiology, 2024)
Spinal cord injury (SCI) is a severe neurological condition that can lead to paralysis or even death. This study explored the potential benefits of bone marrow mesenchymal stem cell (BMSC) transplantation for repairing SCI. BMSCs also differentiate into astrocytes within damaged spinal cord tissues hindering the cell transplantation efficacy, therefore it is crucial to enhance their neuronal differentiation rate to facilitate spinal cord repair. Wnt5a, an upstream protein in the non-classical Wnt signaling pathway, has been implicated in stem cell migration, differentiation, and neurite formation but its role in the neuronal differentiation of BMSCs remains unclear. Thus, this study investigated the role and underlying mechanisms of Wnt5a in promoting neuronal differentiation of BMSCs both in vivo and in vitro. Wnt5a enhanced neuronal differentiation of BMSCs in vitro while reducing astrocyte differentiation. Additionally, high-throughput RNA sequencing revealed a correlation between Wnt5a and phosphoinositide 3-kinase (PI3K)/protein kinase B(AKT) signaling, which was confirmed by the use of the PI3K inhibitor LY294002 to reverse the effects of Wnt5a on BMSC neuronal differentiation. Furthermore, transplantation of Wnt5a-modified BMSCs into SCI rats effectively improved the histomorphology (Hematoxylin and eosin [H&E], Nissl and Luxol Fast Blue [LFB] staining), motor function scores (Footprint test and Basso-Beattie-Bresnahan [BBB]scores)and promoted neuron production, axonal formation, and remodeling of myelin sheaths (microtubule associated protein-2 [MAP-2], growth-associated protein 43 [GAP43], myelin basic protein [MBP]), while reducing astrocyte production (glial fibrillary acidic protein [GFAP]). Therefore, targeting the Wnt5a/PI3K/AKT pathway could enhance BMSC transplantation for SCI treatment.

Comparative analysis of size-fractional eukaryotic microbes in subtropical riverine systems inferred from 18S rRNA gene V4 and V9 regions - Guanglong Zhang; Zhenli Guo; Yue Ke; Hanyi Li; Xilin Xiao; Da Lin; Lujian Lin; Yanhong Wang; Jingchun Liu; Haoliang Lu; Hualong Hong; Chongling Yan (Science of The Total Environment, 2024)

Mechanism of discoloration of Antarctic krill oil upon storage: A study based on model systems - Xiang-Bo Zeng; Xue-Chen Pei; De-Yang Li; Fa-Wen Yin; Hui-Lin Liu; Meng-Ling Jin; Jiang-Hua Zhang; Da-Yong Zhou (Food Chemistry, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Impact of plant and animal proteins with transglutaminase on the gelation properties of clam Meretrix meretrix surimi - Lin-Da Zhang; Lin Li; Qian Zhang; Yu-Qiao Wang; Yue Liu; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Bioscience, 2024)

CXCR3 participates in asymmetric division of mouse oocytes by modulating actin dynamics - Wei-jian Li; Rong-yang Li; Da-yu Wang; Ming Shen; Hong-lin Liu (Theriogenology, 2024)

Surface charge accumulation of functionalized carbonized polymer dots selectively induces lysosomal membrane permeabilization of breast cancer cells - Yu Lei; Bao-Hua Tian; Xin-Xin Li; Ming-Yuan Sun; Xi-Lin Guo; Yi-Da Wang; Hui-Qing Zhou; Ri-Sheng Ma; Hai-Xia Liang (Chemical Engineering Journal, 2024)

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

Simulation of saturated–unsaturated seepage problems via the virtual element method - Yinghao Sun; Da Li; Lei Jiao; Zhongxin Liu; Yun Yang; Junda Lyu; Shan Lin (Computers and Geotechnics, 2024)

Mechanism of color change in Antarctic krill oil during storage - Xiang-Bo Zeng; Fa-Wen Yin; Guan-Hua Zhao; Chao Guo; De-Yang Li; Hui-Lin Liu; Lei Qin; Fereidoon Shahidi; Da-Yong Zhou (Food Chemistry, 2024)

Power improvement of triboelectric nanogenerator by morphological transformation strategy for harvesting irregular wave energy - Jianlong Wang; Zhenjie Wang; Da Zhao; Yang Yu; Xiaojun Cheng; Hengyu Li; Zhong Lin Wang; Tinghai Cheng (Chemical Engineering Journal, 2024)

Losing Tidal Flats at the Midpoint of the East Asian-Australasian Flyway over the past 100 Years - Wan-Jyun Chen; An-Yu Chang; Chia-Chi Lin; Ruey-Shing Lin; Da-Li Lin; Pei-Fen Lee (Wetlands, 2024)
The ecosystem services and functions of tidal flats have been overlooked for many decades, and tidal flat loss has been identified as a serious threat to many taxa in recent years, especially for migratory waterbirds. Despite the understanding of tidal flats change on the global scale, there are still a lot of unknowns on the small scale, including tidal flats in Taiwan, which are important stopover sites for migratory waterbirds along the East Asian–Australasian Flyway. Therefore, we collated historic topographic maps, Landsat Archive images between the 1920s and the 2020s to determine the trajectories of tidal flat change along the coastline of Taiwan. Our results show that tidal flat coverage expanded between the 1920s and the 1950s, but lost approximately 266 km 2 (58%) between the 1950s and the 2010s. The status of the tidal flats along the western coastline of Taiwan has been identified as “Endangered” based on the criteria of the IUCN Red List of Ecosystems. According to the aims of the Global Biodiversity Framework, we suggest rethinking the land use plans along the coastline to mitigate the tidal flat loss, especially the controversial issues concerning the expansion of green energy infrastructure. To realize the Nature Positive goals by 2030, recovering and restoring the tidal flat ecosystem could be one of the key strategies.

PLD2 deletion ameliorates sepsis-induced cardiomyopathy by suppressing cardiomyocyte pyroptosis via the NLRP3/caspase 1/GSDMD pathway - Jun Li; Da Teng; Wenjuan Jia; Lei Gong; Haibin Dong; Chunxiao Wang; Lihui Zhang; Bowen Xu; Wenlong Wang; Lin Zhong; Jianxun Wang; Jun Yang (Inflammation Research, 2024)
Objective Sepsis-induced cardiomyopathy (SICM) is a life-threatening complication. Phospholipase D2 (PLD2) is crucial in mediating inflammatory reactions and is associated with the prognosis of patients with sepsis. Whether PLD2 is involved in the pathophysiology of SICM remains unknown. This study aimed to investigate the effect of PLD2 knockout on SICM and to explore potential mechanisms. Methods The SICM model was established using cecal ligation and puncture in wild-type and PLD2-knockout mice and lipopolysaccharide (LPS)-induced H9C2 cardiomyocytes. Transfection with PLD2-shRNA lentivirus and a PLD2 overexpression plasmid were used to interfere with PLD2 expression in H9C2 cells. Cardiac pathological alterations, cardiac function, markers of myocardial injury, and inflammatory factors were used to evaluate the SICM model. The expression of pyroptosis-related proteins (NLRP3, cleaved caspase 1, and GSDMD-N) was assessed using western blotting, immunofluorescence, and immunohistochemistry. Results SICM mice had myocardial tissue damage, increased inflammatory response, and impaired heart function, accompanied by elevated PLD2 expression. PLD2 deletion improved cardiac histological changes, mitigated cTNI production, and enhanced the survival of the SICM mice. Compared with controls, PLD2-knockdown H9C2 exhibits a decrease in inflammatory markers and lactate dehydrogenase production, and scanning electron microscopy results suggest that pyroptosis may be involved. The overexpression of PLD2 increased the expression of NLRP3 in cardiomyocytes. In addition, PLD2 deletion decreased the expression of pyroptosis-related proteins in SICM mice and LPS-induced H9C2 cells. Conclusion PLD2 deletion is involved in SICM pathogenesis and is associated with the inhibition of the myocardial inflammatory response and pyroptosis through the NLRP3/caspase 1/GSDMD pathway.

Antiproliferative polycyclic polyprenylated acylphloroglucinols from Garcinia paucinervis - Cui-Cui Jia; Jing-Jing Xue; Zhan-Lin Li; Da-Hong Li; Hui-Ming Hua (Natural Product Research, 2024)

Biodegradation of phthalate acid esters and whole-genome analysis of a novel Streptomyces sp. FZ201 isolated from natural habitats - Nai-Xian Feng; Da-Wei Li; Fei Zhang; Hui Bin; Yi-Tong Huang; Lei Xiang; Bai-Lin Liu; Quan-Ying Cai; Yan-Wen Li; De-Lin Xu; Yunchang Xie; Ce-Hui Mo (Journal of Hazardous Materials, 2024)

Distribution of per- and polyfluoroalkyl substances in blood, serum, and urine of patients with liver cancer and associations with liver function biomarkers - Cao Dai; Lin Peng; Yanjie Li; Zhendong Li; Da Chen; Fei Wang; Nan Lin (Journal of Environmental Sciences, 2024)

Micro-structure change and crystal-structure modulated of oxygen carriers for chemical looping: Controlling local chemical environment of lattice oxygen - Da Song; Tao Long; Cuiqin Li; Yang Li; Mingyang Fan; Yonghao Lu; Yuchao Zhou; Haitao Chen; Yan Lin; Zhen Huang; Fang He (Fuel, 2024)

Microcystin-RR promote lipid accumulation through CD36 mediated signal pathway and fatty acid uptake in HepG2 cells - Wenjuan Jia; Lin Zhong; Qingmiao Ren; Da Teng; Lei Gong; Haibin Dong; Jun Li; Chunxiao Wang; Yong-Xing He; Jun Yang (Environmental Research, 2024)

Humic substances mediated superior photochemical pollutant conversion on defective TiO2 in environmentally relevant matrices: The key roles of oxygen vacancy in surface interactions, oxidant activation and radical generation - Song Hu; Lyumeng Ye; Bing-Jie Tian; Jia-Ying Li; Ai-Yong Zhang; Lu Zhao; Chi Zhang; Chu Jiang; Zhi-Xian Lin; Wei Da; Qi-Xin Wei (Science of The Total Environment, 2024)

Effect of liver cancer on the accumulation and hepatobiliary transport of per- and polyfluoroalkyl substances - Ying Liu; Lin Peng; Yanjie Li; Xingwen Lu; Fei Wang; Da Chen; Nan Lin (Journal of Hazardous Materials, 2024)

The longevity evaluation of multi-metal stabilization by MgO in Pb/Zn smelter–contaminated soils - Ze-Lin Xu; Da-Mao Xu; Hai-Xuan Li; Hao-Kai Li; Rong-Bing Fu (Environmental Science and Pollution Research, 2024)

Inhibition of quorum sensing serves as an effective strategy to mitigate the risks of human bacterial pathogens in soil - Jinghan Zhang; Kun Lu; Lin Zhu; Na Li; Da Lin; Yangjuan Cheng; Meizhen Wang (Journal of Hazardous Materials, 2024)

Advancements and hurdles of deeper‐offshore aquaculture in China - Shuang‐Lin Dong; Yun‐Wei Dong; Liu‐Yi Huang; Yan‐Gen Zhou; Ling Cao; Xiang‐Li Tian; Li‐Min Han; Da‐Hai Li (Reviews in Aquaculture, 2024)
Open offshore areas boast strong physical self‐purification capacity and abundant non‐fossil energy resources, such as wind, waves, and solar energy. Consequently, the global community anticipates nearshore aquaculture to transition towards offshore to help increase production, alleviate eutrophication, and reduce greenhouse gas emissions. To date, China has constructed over 40 sets of deeper‐offshore aquaculture (DOA) infrastructures, encompassing various types of pens, cages and closed containment systems. Although DOA holds vast potential to address food security and aquaculture sustainability in China, its current development trajectory struggles to meet those goals and primarily achieves profitability by focusing on high‐value species or products. For DOA to realize its potential, innovative production systems must tackle three key contradictions: enterprise profitability versus product affordability, clean energy‐based products versus carbon‐intensive products, and automated operation versus re‐employment of coastal fish farmers. Resolving these contradictions requires the development of a large‐scale, anti‐typhoon offshore enclosure that integrates mariculture with other industries, such as wind farming, food processing, and tourism. This approach will foster a sustainable balance between profitability, environmental impact, and employment opportunities in the sector.

Membrane lipid remodeling and autophagy to cope with phosphorus deficiency in the dinoflagellate Prorocentrum shikokuense - Da-Wei Li; Jin-Zhou Tan; Zhuo-Fan Li; Lin-Jian Ou (Chemosphere, 2024)

Application of proteomics in identifying crucial virulence factors shared by different Streptococcus iniae isolates for developing an effective subunit vaccine against S. iniae in tilapia - Chaio-Ping Chen; Shu-Chun Chuang; Kuan-Lun Su; Li-Kai Chen; Yi-Chen Lin; Yu-Jen Wu; Shang-Pin Liu; Shao-Wen Hung; Chung-Hwan Chen; Chung-Da Yang (Aquaculture, 2024)

Characterization of microbial contamination in agricultural soil: A public health perspective - Xiaodi Li; Lin Zhu; Si-Yu Zhang; Jingpeng Li; Da Lin; Meizhen Wang (Science of The Total Environment, 2024)

Triclocarban exhibits higher adipogenic activity than triclosan through peroxisome proliferator-activated receptors pathways - Jia-Da Zhang; Sen He; Ting-Ting He; Chuan-Hai Li; Bing-Hua Yan; Yuan Yang; Jian Yang; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Environmental Pollution, 2024)

Mechanical robust, adhesive, self-healable and biodegradable protein-based electronic skin sensors for smart elderly care - Ying-Ao Zhang; Chen-Yu Wang; Xiao-Xue Wang; Meng Yin; Ke Wang; Da-Wei Zhou; Hong-Long Zheng; Shou-Shan Yu; Shuang Li; Ke-Zheng Chen; Sheng-Lin Qiao (Chemical Engineering Journal, 2024)

Simultaneous generation of free radicals, Fe(IV) and Fe(V) by ferrate activation: A review - Feilong Dong; Chuyun Fu; Mingbao Feng; Da Wang; Shuang Song; Cong Li; Eric Lichtfouse; Jinzhe Li; Qiufeng Lin; Virender K. Sharma (Chemical Engineering Journal, 2024)

A two-stage Fe(VI) oxidation process enhances the removal of bisphenol A for potential application - Feilong Dong; Chuyun Fu; Zhu Meng; Qiufeng Lin; Jinzhe Li; Tao Zeng; Da Wang; Juntao Tang; Shuang Song (Science of The Total Environment, 2024)

The apple lipoxygenase MdLOX3 positively regulates zinc tolerance - Guo-Lin Chen; Da-Ru Wang; Xin Liu; Xun Wang; Hao-Feng Liu; Chun-Ling Zhang; Zhen-Lu Zhang; Lin-Guang Li; Chun-Xiang You (Journal of Hazardous Materials, 2024)

How do the occurrence patterns of potentially toxic elements (PTEs) control their release behaviours from Pb/Zn smelter contaminated soils? - Da-Mao Xu; Hao-Kai Li; Ze-Lin Xu; Rong-Bing Fu (Journal of Cleaner Production, 2024)

Toll-Like Receptor 4 Deficiency Ameliorates Propofol-Induced Impairments of Cognitive Function and Synaptic Plasticity in Young Mice - Qiao-Ding Dai; Kang-Song Wu; Li-Ping Xu; Yan Zhang; Na Lin; Yao Jiang; Chong-Yu Shao; Li-Da Su (Molecular Neurobiology, 2024)

Differences in endophytic bacterial and fungal compositions in roots between red and green Amaranthus sp. - Da Yang; Xinru Lin; Xinyan Zhou; Zujian Li; Hiromi Kurokawa; Hirofumi Matsui; Toyohisa Fujita; Shang-Dong Yang (South African Journal of Botany, 2023)

Toxic vascular effects of polystyrene microplastic exposure - Jianlong Yan; Yanbin Pan; Junbo He; Xinli Pang; Wenming Shao; Caiping Wang; Rongning Wang; Yaqiong He; Min Zhang; Juheng Ye; Chaolan Lin; Feng Lin; et al. (Science of The Total Environment, 2023)

Widespread clay authigenesis and highly congruent silicate weathering in the Marinoan aftermath - Yi-Sheng Yin; Guang-Yi Wei; Philip A.E. Pogge von Strandmann; Maxwell A. Lechte; Simon V. Hohl; Yi-Bo Lin; Da Li; Tianyu Chen; Tao Yang; Feifei Zhang; Terry T. Isson; He Zhang; et al. (Earth and Planetary Science Letters, 2023)

Spatial bandgap tailoring via a novel injection chemical bath deposition enables highly efficient carbon-based Sb2(S,Se)3 thin film solar cells - Peng Tang; Zi-Heng Huang; You-Xian Chen; Hu Li; Li-Quan Yao; Hui Li; Li-Mei Lin; Jin-Rui Cai; Ya-Lu Zhan; Dong Wei; Shui-Yuan Chen; Da-Qin Chen; et al. (Chemical Engineering Journal, 2023)

Polyphenols modulate microalgae metabolism with a particular increment in lipid accumulation - Li-Gong Zou; Dan-Lin Zheng; Yi-Tong Yao; Fu-Fang Wen; Da-Wei Li; Yu-Feng Yang; Wei-Dong Yang; Srinivasan Balamurugan; Hang Fai Kwok; Hong-Ye Li (Fuel, 2023)

Metformin improves sheep sperm cryopreservation via vitalizing the AMPK pathway - Xing Zhang; Song-Mao Guo; Da-Wei Zhu; Yu Li; Fei Wen; Ming Xian; Zhang-Tao Hu; Qian-Long Zou; Li-Kun Zhang; Yu-Lin Chen; Jian-Hong Hu (Theriogenology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

The occurrence of "yellowing" phenomenon and its main driving factors after the remediation of chromium (Cr)-contaminated soils: A literature review - Hao-Kai Li; Da-Mao Xu; Jun-Xian Wang; Ze-Lin Xu; Rong-Bing Fu (Journal of Hazardous Materials, 2023)

Effect of copper ions on transformation of organic sulfur in cationic exchange resins in Li2CO3–Na2CO3–K2CO3 molten-salt system - Zhi Zhang; Yun Xue; Yue-Lin Wang; Wen-Da Xu; Yong-De Yan; Yang-Hai Zheng; Fu-Qiu Ma; Guo-Qiang Li (Chemosphere, 2023)

Industrial symbiosis promoting material exchanges in Ulan Buh Demonstration Eco-industrial Park: A multi-objective MILP model - Hao Yu; Lin Da; Yalun Li; Yanqiong Chen; Qingdan Geng; Zhibin Jia; Yun Zhang; Jinhua Li; Caixia Gao (Journal of Cleaner Production, 2023)

Fe(VI) activation system mediated by a solar-driven TiO2 nanotubes electrode for CLQ degradation: Performances, mechanisms and pathways - Jinzhe Li; Chuyun Fu; Qiufeng Lin; Tao Zeng; Da Wang; Xinwen Huang; Shuang Song; Cong Li; Feilong Dong (Journal of Hazardous Materials, 2023)

Enhanced selective separation of vanadium(V) and chromium(VI) using the CeO2 nanorod containing oxygen vacancies - Ruixi Lin; Jiarong Li; Xuequan Jing; Meina Guo; Guoqing Ren; Haonan Qin; Zhangwei Yao; Yinhua Wan; Weijie Song; Huifeng Zeng; Feifei Yang; Da Zhao; et al. (Environmental Science and Pollution Research, 2023)

Multiple ocean oxygenation events during the Ediacaran Period: Mo isotope evidence from the Nanhua Basin, South China - Lin Yuan; Ying Zhou; Xi Chen; Maoyan Zhu; Simon W. Poulton; Zheyu Tian; Da Li; Matthew Thirlwall; Graham A. Shields (Precambrian Research, 2023)

Elucidating colony bloom formation mechanism of a harmful alga Phaeocystis globosa (Prymnesiophyceae) using metaproteomics - Hua-Min Cheng; Shu-Feng Zhang; Xiao-Lian Ning; Jian-Xiang Peng; Dong-Xu Li; Hao Zhang; Kun Zhang; Lin Lin; Si-Qi Liu; Walker O. Smith; Da-Zhi Wang (Science of The Total Environment, 2023)

Effects of low salinity stress on osmoregulation and gill transcriptome in different populations of mud crab Scylla paramamosain - Wen-Bin Xu; Yan-Mei Zhang; Bang-Ze Li; Chen-Yang Lin; Da-Yong Chen; Yuan-Xin Cheng; Xiao-Ling Guo; Wei-Ren Dong; Miao-An Shu (Science of The Total Environment, 2023)

Ultrapotassic enclaves in the Miocene adakitic granitoids, southern Tibet: Direct evidence for collision-related crust-mantle interaction and its implications - Chang-da Wu; Yuan-chuan Zheng; Bo Xu; Zeng-qian Hou; Peng Chai; Xin Li; Lin-yuan Zhang; Zi-xuan Wang; Lu Wang; Yang Shen (Lithos, 2023)

Effect of defects in adhesive layer on the interfacial bond behaviors of externally bonded CFRP-to-concrete joints - Peng-Da Li; Yao Zhao; Yu-Fei Wu; Jian-Ping Lin (Engineering Structures, 2023)

Performance and application of a novel drainage anti-slide pile on accumulation landslide with a chair-like deposit-bedrock interface in the Three Gorges Reservoir area, China - Shi-lin Luo; Da Huang; Jian-bing Peng; Ailifeila Aierken; Zhao Li; Xi-bin Kuang; Roberto Tomás (Computers and Geotechnics, 2023)

Improving the genome and proteome annotations of the marine model diatom Thalassiosira pseudonana using a proteogenomics strategy - Xiao-Huang Chen; Ming-Kun Yang; Yuan-Yuan Li; Zhang-Xian Xie; Shu-Feng Zhang; Mats Töpel; Shady A. Amin; Lin Lin; Feng Ge; Da-Zhi Wang (Marine Life Science & Technology, 2023)
Diatoms are unicellular eukaryotic phytoplankton that account for approximately 20% of global carbon fixation and 40% of marine primary productivity; thus, they are essential for global carbon biogeochemical cycling and climate. The availability of ten diatom genome sequences has facilitated evolutionary, biological and ecological research over the past decade; however, a complimentary map of the diatom proteome with direct measurements of proteins and peptides is still lacking. Here, we present a proteome map of the model marine diatom Thalassiosira pseudonana using high-resolution mass spectrometry combined with a proteogenomic strategy. In-depth proteomic profiling of three different growth phases and three nutrient-deficient samples identified 9526 proteins, accounting for ~ 81% of the predicted protein-coding genes. Proteogenomic analysis identified 1235 novel genes, 975 revised genes, 104 splice variants and 234 single amino acid variants. Furthermore, our quantitative proteomic analysis experimentally demonstrated that a considerable number of novel genes were differentially translated under different nutrient conditions. These findings substantially improve the genome annotation of T. pseudonana and provide insights into new biological functions of diatoms. This relatively comprehensive diatom proteome catalog will complement available diatom genome and transcriptome data to advance biological and ecological research of marine diatoms.

Triclocarban and triclosan exacerbate high-fat diet-induced hepatic lipid accumulation at environmental related levels: The potential roles of estrogen-related receptors pathways - Xin Li; Jia-Da Zhang; Han Xiao; Sen He; Ting-Ting He; Xiao-Min Ren; Bing-Hua Yan; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2023)

Nitric Oxide Alleviates Submergence-Induced Maize Seedling Root Tip Cell Death - Yaoqi Li; Qiong Nan; Yinai Liu; Sue Lin; Hao Ji; Da Sun; Libo Jin; Renyi Peng (Journal of Plant Growth Regulation, 2023)

Stilbenes with potent cytotoxicity from the seedcases of Paeonia suffruticosa Andrews - Meng-Yue Yang; Zhao-Xiang Shao; Yue-Tong Wang; Yong-Lian Hou; Ding-Kang Zhu; Sha Chen; Ya-Hui Zhang; Fei Cao; Yong-Kui Jing; Bin Lin; Zhan-Lin Li; Da-Hong Li; et al. (Phytochemistry, 2023)

Crocin Alleviates Intracerebral Hemorrhage–Induced Neuronal Ferroptosis by Facilitating Nrf2 Nuclear Translocation - Fei Wang; Wu-lin Li; Li-juan Shen; Ting-ting Jiang; Jian-jun Xia; Da-li You; Shan-you Hu; Li Wang; Xiao Wu (Neurotoxicity Research, 2022)

Transcriptomic analyses provide insight into adventitious root formation of Euryodendron excelsum H. T. Chang during ex vitro rooting - Yuping Xiong; Shuangyan Chen; Zhenpeng Wei; Xiaohong Chen; Beiyi Guo; Ting Zhang; Yuying Yin; Xincheng Yu; Jinhui Pang; Meiyun Niu; Xinhua Zhang; Yuan Li; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Estimation of permafrost thermal behavior using Fourier series model - Yan-yu Zhang; Shu-ying Zang; Lin Zhao; Da-long Ma; Yue Lin; Hao Li (Journal of Mountain Science, 2022)

On the Diurnal Cycle of Heavy Rainfall over the Sichuan Basin during 10–18 August 2020 - Rudi Xia; Yali Luo; Da-Lin Zhang; Mingxin Li; Xinghua Bao; Jisong Sun (Advances in Atmospheric Sciences, 2021)
A sustained heavy rainfall event occurred over the Sichuan basin in southwest China during 10–18 August 2020, showing pronounced diurnal rainfall variations with nighttime peak and afternoon minimum values, except on the first day. Results show that the westward extension of the anomalously strong western Pacific subtropical high was conducive to the maintenance of a southerly low-level jet (LLJ) in and to the southeast of the basin, which favored continuous water vapor transport and abnormally high precipitable water in the basin. The diurnal cycle of rainfall over the basin was closely related to the periodic oscillation of the LLJ in both wind speed and direction that was caused by the combination of inertial oscillation and terrain thermal forcing. The nocturnally enhanced rainfall was produced by moist convection mostly initiated during the evening hours over the southwest part of the basin where high convective available potential energy with moister near-surface moist air was present. The convective initiation took place as cold air from either previous precipitating clouds from the western Sichuan Plateau or a larger-scale northerly flow met a warm and humid current from the south. It was the slantwise lifting of the warm, moist airflow above the cold air, often facilitated by southwest vortices and quasi-geostrophic ascent, that released the convective instability and produced heavy rainfall.

The mechanism and application of high-pressure water jet technology to prevent compound dynamic disaster - Zeng-qiang Yang; Chang Liu; Feng-shuo Li; Lin-ming Dou; Gang-wei Li; Da-wei Wang (Arabian Journal of Geosciences, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Mixture of Pb, Zn and Cu on root permeability and radial oxygen loss in the mangrove Bruguiera gymnorrhiza - Hao Cheng; You-Shao Wang; Chang-Da Li; Zhi-Hong Ye; Shafi Muhammad; Mei-Lin Wu; Fun-Lin Sun (Ecotoxicology, 2020)

Dynamics of radial oxygen loss in mangroves subjected to waterlogging - Hao Cheng; Mei-Lin Wu; Chang-Da Li; Fu-Lin Sun; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Contamination characteristics of heavy metals in particle size fractions from street dust from an industrial city, Central China - Ping Zhong; Jia-Quan Zhang; Da-Mao Xu; Qian Tian; Tian-Peng Hu; Xiang-Yi Gong; Chang-Lin Zhan; Shan Liu; Xin-Li Xing; Shi-Hua Qi (Air Quality, Atmosphere & Health, 2020)

Sideswiping Tropical Cyclones and Their Associated Precipitation over China - Tian Feng; Fumin Ren; Da-Lin Zhang; Guoping Li; Wenyu Qiu; Hui Yang (Advances in Atmospheric Sciences, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Effects of long-term planting on PhytOC storage and its distribution in soil physical fractions in Moso bamboo forests in subtropical China - Chengpeng Huang; Yongchun Li; Lin Jin; Xiaoqiang Gong; Jiasen Wu; Da Dong; Scott X. Chang; Peikun Jiang (Journal of Soils and Sediments, 2020)

The Cannabinoid Receptor Agonist WIN55,212-2 Ameliorates Hippocampal Neuronal Damage After Chronic Cerebral Hypoperfusion Possibly Through Inhibiting Oxidative Stress and ASK1-p38 Signaling - Da-Peng Wang; Qiao-Li Lv; Qi Lin; Kai Kang; Kai-Yan Jin; Jian Hai (Neurotoxicity Research, 2020)

Contrasting the Pb (II) and Cd (II) tolerance of Enterobacter sp. via its cellular stress responses - Zhongquan Jiang; Liu Jiang; Lin Zhang; Mu Su; Da Tian; Tong Wang; Yalin Sun; Ying Nong; Shuijin Hu; Shimei Wang; Zhen Li (Environmental Microbiology, 2020)
Summary Successful application of microorganisms to heavy metal remediation depends on their resistance to toxic metals. This study contrasted the differences of tolerant mechanisms between Pb 2+ and Cd 2+ in Enterobacter sp. Microbial respiration and production of formic acid showed that Enterobacter sp. had a higher tolerant concentration of Pb (>1000 mg l −1 ) than Cd (about 200 mg l −1 ). Additionally, SEM confirmed that most of Pb and Cd nanoparticles (NPs) were adsorbed onto cell membrane. The Cd stress, even at low concentration (50 mg l −1 ), significantly enlarged the sizes of cells. The cellular size raised from 0.4 × 1.0 to 0.9 × 1.6 μm on average, inducing a platelet‐like shape. In contrast, Pb cations did not stimulate such enlargement even up to 1000 mg l −1 . Moreover, Cd NPs were adsorbed homogeneously by almost all the bacterial cells under TEM. However, only a few cells work as ‘hot spots’ on the sorption of Pb NPs. The heterogeneous sorption might result from a ‘self‐sacrifice’ mechanism, i.e., some cells at a special life stage contributed mostly to Pb sorption. This mechanism, together with the lower mobility of Pb cations, caused higher microbial tolerance and removal efficiency towards Pb 2+ . This study sheds evident contrasts of bacterial resistance to the two most common heavy metals.

Coordinated Variation of Contact Angles During Mobilization of Double Liquid–Gas Interfaces in a Microcapillary - Da Lei; Mian Lin; Yun Li; Wenbin Jiang (Transport in Porous Media, 2020)

Cadmium immobilization in aqueous solution by Aspergillus niger and geological fluorapatite - Christopher Uche Okolie; Haoming Chen; Yexin Zhao; Da Tian; Lin Zhang; Mu Su; Zhonquan Jiang; Zhen Li; Huixin Li (Environmental Science and Pollution Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Protective role of curcumin in cadmium-induced testicular injury in mice by attenuating oxidative stress via Nrf2/ARE pathway - Shu-Hua Yang; Jian-Bin He; Li-Hui Yu; Lin Li; Miao Long; Ming-Da Liu; Peng Li (Environmental Science and Pollution Research, 2019)

Isochromanes from Aspergillus fumigatus , an endophytic fungus from Cordyceps sinensis - Xiao-Hua Li; Xue-Hua Han; Ling-Ling Qin; Jun-Lin He; Zhi-Xing Cao; Yu-Cheng Gu; Da-Le Guo; Yun Deng (Natural Product Research, 2019)

A Two-Step GRIN Lens Coating for In Vivo Brain Imaging - Yupeng Yang; Lifeng Zhang; Zhenni Wang; Bo Liang; Giovanni Barbera; Casey Moffitt; Yun Li; Da-Ting Lin (Neuroscience Bulletin, 2019)

Fluids discrimination by ray-path elastic impedance inversion: A successful case from Sulige tight gas field - Da-Xing Wang; Hao-Fan Wang; Jin-Feng Ma; Yong-Gang Wang; Na Zhang; Lin Li (Applied Geophysics, 2019)

Applications of Raman spectroscopic techniques for quality and safety evaluation of milk: A review of recent developments - Huirong He; Da-Wen Sun; Hongbin Pu; Lijun Chen; Li Lin (Critical Reviews in Food Science and Nutrition, 2019)

Population pharmacokinetics of oxcarbazepine active metabolite in Chinese paediatric epilepsy patients and its application in individualised dosage regimens - Wei-wei Lin; Xi-wen Li; Zheng Jiao; Jin Zhang; Xin Rao; Da-yong Zeng; Xin-hua Lin; Chang-lian Wang (European Journal of Clinical Pharmacology, 2019)

Provenance of the Langjiexue Group to the south of the Yarlung-Tsangpo Suture Zone in southeastern Tibet: Insights on the evolution of the Neo-Tethys Ocean in the Late Triassic - Da-Ren Fang; Gen-Hou Wang; Ken-ichiro Hisada; Guo-Li Yuan; Fang-Lin Han; Dian Li; Yu Tang; Qiu-Ming Pei; Liang-Liang Zhang (International Geology Review, 2019)

A new insight into lead (II) tolerance of environmental fungi based on a study of Aspergillus niger and Penicillium oxalicum - Da Tian; Zhongquan Jiang; Liu Jiang; Mu Su; Zheye Feng; Lin Zhang; Shimei Wang; Zhen Li; Shuijin Hu (Environmental Microbiology, 2019)
Summary Environmental microorganisms have been widely applied in heavy metal remediation. This study explored the mechanisms of lead tolerance of two typical filamentous fungi, Aspergillus niger and Penicillium oxalicum . It is shown that the mechanisms of reducing Pb toxicity by these two fungi have three major pathways. The secreted oxalic acid can react with Pb (II) to form insoluble Pb minerals, primarily lead oxalate. Then, the enhanced biosorption via forming new border of cell wall prevents the transportation of Pb (II) into hypha. In addition, the fungal activity could be maintained even at high Pb concentration due to the intracellular accumulation. It was confirmed that A. niger has the higher Pb tolerance (up to 1500 mg l −1 Pb level) compared with P. oxalicum (up to 1000 mg l −1 ). Meanwhile, Pb levels below 1000 mg l −1 partially stimulate the bioactivity of A. niger , which was confirmed by its elevated respiration (from 53 to 63 mg C l −1 medium h −1 ). This subsequently enhanced microbial functions of A. niger to resist Pb toxicity. A better understanding of Pb tolerance of these two fungi sheds a bright future of applying them to remediate lead‐contaminated environments.

Contamination characteristics and potential environmental implications of heavy metals in road dusts in typical industrial and agricultural cities, southeastern Hubei Province, Central China - Da-Mao Xu; Jia-Quan Zhang; Bo Yan; Hao Liu; Li-Li Zhang; Chang-Lin Zhan; Li Zhang; Ping Zhong (Environmental Science and Pollution Research, 2018)

Impacts of Land Cover Changes on Ecosystem Carbon Stocks Over the Transboundary Tumen River Basin in Northeast Asia - Hengxing Xiang; Mingming Jia; Zongming Wang; Lin Li; Dehua Mao; Da Zhang; Guishan Cui; Weihong Zhu (Chinese Geographical Science, 2018)

Depositional sequence response to Paleogene Lake level and Paleoclimate changes in the northern Liaoxi depression, eastern China - Nanan Gao; Changsong Lin; Da Gao; Hong Li (Arabian Journal of Geosciences, 2018)

Metatranscriptome analysis reveals environmental and diel regulation of a Heterosigma akashiwo (raphidophyceae) bloom - Nanjing Ji; Lingxiao Lin; Ling Li; Liying Yu; Yaqun Zhang; Hao Luo; Meizhen Li; Xinguo Shi; Da‐Zhi Wang; Senjie Lin (Environmental Microbiology, 2018)
Summary Despite numerous laboratory studies on physiologies of harmful algal bloom (HAB) species, physiologies of these algae during a natural bloom are understudied. Here, we investigated a bloom of the raphidophyte Heterosigma akashiwo in the East China Sea in 2014 using metabarcode (18S rDNA) and metatranscriptome sequencing. Based on 18S rDNA analyses, the phytoplankton community shifted from high diversity in the pre‐bloom stage to H. akashiwo predominance during the bloom. A sharp decrease in ambient dissolved inorganic phosphate and strong up‐regulation of phosphate and dissolved organic phosphorus (DOP) uptake genes, including the rarely documented (ppGpp)ase, in H. akashiwo from pre‐bloom to bloom was indicative of rapid phosphorus uptake and efficient utilization of DOP that might be a driver of the H. akashiwo bloom. Furthermore, observed up‐regulated expression of mixotrophy‐related genes suggests potential contribution of mixotrophy to the bloom. Accelerating photosynthetic carbon fixation was also implied by the up‐regulation of carbonic anhydrase genes during the bloom. Notably, we also observed a strong morning‐to‐afternoon shift in the expression of many genes. Our findings provide insights into metabolic processes likely important for H. akashiwo bloom formation, and suggest the need to consider timing of sampling in field studies on this alga.

Metaproteomics reveals major microbial players and their metabolic activities during the blooming period of a marine dinoflagellate Prorocentrum donghaiense - Dong‐Xu Li; Hao Zhang; Xiao‐Huang Chen; Zhang‐Xian Xie; Yong Zhang; Shu‐Feng Zhang; Lin Lin; Feng Chen; Da‐Zhi Wang (Environmental Microbiology, 2018)
Summary Interactions between bacteria and phytoplankton during bloom events are essential for both partners, which impacts their physiology, alters ambient chemistry and shapes ecosystem diversity. Here, we investigated the community structure and metabolic activities of free‐living bacterioplankton in different blooming phases of a dinoflagellate Prorocentrum donghaiense using a metaproteomic approach. The Fibrobacteres ‐ Chlorobi ‐ Bacteroidetes group, Rhodobacteraceae , SAR11 and SAR86 clades contributed largely to the bacterial community in the middle‐blooming phase while the Pseudoalteromonadaceae exclusively dominated in the late‐blooming phase. Transporters and membrane proteins, especially TonB‐dependent receptors were highly abundant in both blooming phases. Proteins involved in carbon metabolism, energy metabolism and stress response were frequently detected in the middle‐blooming phase while proteins participating in proteolysis and central carbon metabolism were abundant in the late‐blooming phase. Beta‐glucosidase with putative algicidal capability was identified from the Pseudoalteromonadaceae only in the late‐blooming phase, suggesting an active role of this group in lysing P . donghaiense cells. Our results indicated that diverse substrate utilization strategies and different capabilities for environmental adaptation among bacteria shaped their distinct niches in different bloom phases, and certain bacterial species from the Pseudoalteromonadaceae might be crucial for the termination of a dinoflagellate bloom.

A statistical analysis of hourly heavy rainfall events over the Beijing metropolitan region during the warm seasons of 2007–2014 - Huiqi Li; Xiaopeng Cui; Da‐Lin Zhang (International Journal of Climatology, 2017)
A statistical analysis of the spatiotemporal characteristics of hourly heavy rainfall ( HHR ) events and rainstorm days, defined as greater than 20 mm h −1 and 50 mm day −1 , respectively, is performed using observations at 5‐min intervals from 155 automated weather stations ( AWSs ) over the Beijing metropolitan region ( BMR ) during the warm seasons of 2007–2014. Results show pronounced variability in the frequencies and rainfall amounts of both HHR events and rainstorm days across the BMR of less than 150 km width from the west to east. That is, higher‐ (lower) frequency HHR events with more (less) accumulated rainfall amounts take place in eastern Haidian and over the BMR 's northeast mountains (west and northwest mountains). Many extreme rainfall and even record‐breaking events, in terms of the frequency, duration, rainfall amount and intensity, are found to occur in the regions of high‐frequency HHR events and rainstorm days. The frequency of rainstorm days with HHR events accounts for more than 50% of that of total rainstorm days over the BMR 's plains and near the northeast mountains. Results also show that HHR events occur most frequently in late July, and typically peak during 1600–2000 LST . A comparison of the averaged surface meteorological variables and upper‐air sounding at 0800 LST between HHR and non‐ HHR days reveals that the occurrences of the HHR events coincide with the distribution of surface warmer and more humid air as well as organized convergence in the presence of an unstable environment with surface south‐ to southeasterly winds, low‐level south to southwesterly flows and a deep layer of higher moisture content. These results suggest likely the positive influences of urban environment and mountain‐plain circulations on the generation of the HHR events, given favourable larger‐scale conditions.

Overexpression of Arabidopsis ICR1 gene affects vegetative growth and anthesis - Da-Hui Li; Man-Li Li; Xiao-Bo Yu; Di Wu; Huan Xi; Yi Lin; Yong-Ping Cai (Biologia, 2017)

Transient Receptor Potential-canonical 1 is Essential for Environmental Enrichment-Induced Cognitive Enhancement and Neurogenesis - Lai-Ling Du; Lin Wang; Xi-Fei Yang; Ping Wang; Xiao-Hong Li; Da-Min Chai; Bing-Jin Liu; Yun Cao; Wei-Qi Xu; Rong Liu; Qing Tian; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2017)

Celastrol, produced by Tripterygium wilfordii Hook F. enhances defense response in cucumber seedlings against diverse environmental stresses - Li-jun Zhu; Xing-guang Deng; Li-juan Zou; Peng-xu Li; Jun-qiang Wu; Da-wei Zhang; Honghui Lin (Journal of Plant Biology, 2017)

Dissipation of excess excitation energy of the needle leaves in Pinus trees during cold winters - AO Zhang; Zhen-Hai Cui; Jia-Lin Yu; Zi-Ling Hu; Rui Ding; Da-Ming Ren; Li-Jun Zhang (International Journal of Biometeorology, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Ordovician intrusive rocks from the eastern Central Asian Orogenic Belt in Northeast China: chronology and implications for bidirectional subduction of the early Palaeozoic Palaeo-Asian Ocean - Hongying Li; Zhiguang Zhou; Pengju Li; Da Zhang; Changfeng Liu; XiaoQi Zhao; Lizhen Chen; Congnan Gu; Tingting Lin; Mengmeng Hu (International Geology Review, 2016)

Human amniotic epithelial stem cells promote wound healing by facilitating migration and proliferation of keratinocytes via ERK, JNK and AKT signaling pathways - Bin Zhao; Jia-Qi Liu; Zhao Zheng; Jun Zhang; Shu-Yue Wang; Shi-Chao Han; Qin Zhou; Hao Guan; Chao Li; Lin-Lin Su; Da-Hai Hu (Cell and Tissue Research, 2016)

New naphthopyrones from marine-derived fungus Aspergillus niger 2HL-M-8 and their in vitro antiproliferative activity - Da-Hong Li; Tong Han; Li-Ping Guan; Jiao Bai; Nan Zhao; Zhan-Lin Li; Xin Wu; Hui-Ming Hua (Natural Product Research, 2016)

Changes in the activities of starch metabolism enzymes in rice grains in response to elevated CO2 concentration - Li-Yong Xie; Er-Da Lin; Hong-Liang Zhao; Yong-Xiang Feng (International Journal of Biometeorology, 2016)

Proanthocyanidins accelerate the germination of cucumber (Cucumis sativus L.) seeds - Li-jun Zhu; Xing-guang Deng; Li-juan Zou; Jun-qiang Wu; Da-wei Zhang; Hong-hui Lin (Journal of Plant Biology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Notch2 signaling contributes to cell growth, invasion, and migration in salivary adenoid cystic carcinoma - Jing Qu; Min Song; Jian Xie; Xiao-Yu Huang; Xiao-Meng Hu; Rui-Huan Gan; Yong Zhao; Li-Song Lin; Jiang Chen; Xu Lin; Da-Li Zheng; You-Guang Lu (Molecular and Cellular Biochemistry, 2016)

α7nAChR is expressed in satellite cells at different myogenic status during skeletal muscle wound healing in rats - Zhi-Ling Tian; Shu-Kun Jiang; Miao Zhang; Meng Wang; Jiao-Yong Li; Rui Zhao; Lin-Lin Wang; Min Liu; Shan-Shan Li; Meng-Zhou Zhang; Da-Wei Guan (Journal of Molecular Histology, 2015)

Expression and Functional Analysis of a Pathogenesis-Related Protein 1 Gene, TcLr19PR1, Involved in Wheat Resistance Against Leaf Rust Fungus - Lin Gao; Shen Wang; Xiao-Ying Li; Xue-Jun Wei; Yan-Jun Zhang; Hai-Yan Wang; Da-Qun Liu (Plant Molecular Biology Reporter, 2015)

Mechanism of mining subsidence in coal mining area with thick alluvium soil in China - Da-Wei Zhou; Kan Wu; Gong-Lin Cheng; Liang Li (Arabian Journal of Geosciences, 2015)

Association of novelty-related behaviors and intravenous cocaine self-administration in Diversity Outbred mice - Price E. Dickson; Juliet Ndukum; Troy Wilcox; James Clark; Brittany Roy; Lifeng Zhang; Yun Li; Da-Ting Lin; Elissa J. Chesler (Psychopharmacology, 2015)

Three-dimensional tensor controlled-source electromagnetic modeling based on the vector finite-element method - Ying-Cai Hu; Tong-Lin Li; Cui-Song Fan; Da-Yong Wang; Jian-Ping Li (Applied Geophysics, 2015)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Complete genome sequence analysis identifies a new genotype of brassica yellows virus that infects cabbage and radish in China - Xiao-Yan Zhang; Hai-Ying Xiang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2014)

Migration of Ti from nano-TiO 2 -polyethylene composite packaging into food simulants - Qin-Bao Lin; He Li; Huai-Ning Zhong; Quan Zhao; Da-Hui Xiao; Zhi-Wei Wang (Food Additives & Contaminants: Part A, 2014)

Genomic comparison of Salmonella typhimurium DT104 with non-DT104 strains - Er-Ying Zhao; Hong-Xia Bao; Le Tang; Qing-Hua Zou; Wei-Qiao Liu; Da-Ling Zhu; Jessica Chin; Ying-Ying Dong; Yong-Guo Li; Feng-Lin Cao; Cornelis Poppe; Kenneth E. Sanderson; et al. (Molecular Genetics and Genomics, 2013)

Immunologic Mechanism of Patchouli Alcohol Anti-H1N1 Influenza Virus May Through Regulation of the RLH Signal Pathway In Vitro - Xian-Lin Wu; Da-Hong Ju; Jia Chen; Bin Yu; Kang-Li Liu; Jin-Xiong He; Cong-Qi Dai; Sha Wu; Zhou Chang; You-Ping Wang; Xiao-Yin Chen (Current Microbiology, 2013)

Bird species migration ratio in East Asia, Australia, and surrounding islands - Yiliang Kuo; Da-Li Lin; Fu-Man Chuang; Pei-Fen Lee; Tzung-Su Ding (The Science of Nature, 2013)

Particle swarm optimization algorithm for analyzing SNP–SNP interaction of renin-angiotensin system genes against hypertension - Shyh-Jong Wu; Li-Yeh Chuang; Yu-Da Lin; Wen-Hsien Ho; Fu-Tien Chiang; Cheng-Hong Yang; Hsueh-Wei Chang (Molecular Biology Reports, 2013)

SIRT1 interacts with metabolic transcriptional factors in the pancreas of insulin-resistant and calorie-restricted rats - Yong-Ru Chen; Yu-lin Lai; Shao-da Lin; Xi-tao Li; Yu-Cai Fu; Wen-Can Xu (Molecular Biology Reports, 2013)

Prevalence of type-specific human papillomavirus and pap results in Chinese women: a multi-center, population-based cross-sectional study - En-Qi Wu; Bin Liu; Jian-Feng Cui; Wen Chen; Jian-Bing Wang; Liang Lu; Mayineur Niyazi; Chao Zhao; Sheng-Da Ren; Chang-Qing Li; Xiang-Zhen Gong; Jennifer S. Smith; et al. (Cancer Causes & Control, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

The joint effect of cigarette smoking and polymorphisms on LRP5, LEPR, near MC4R and SH2B1 genes on metabolic syndrome susceptibility in Taiwan - Chuan-Wei Yang; Chia-Ing Li; Chiu-Shong Liu; Da-Tian Bau; Chih-Hsueh Lin; Wen-Yuan Lin; Tsai-Chung Li; Cheng-Chieh Lin (Molecular Biology Reports, 2013)

Structure and evolution of the mitochondrial genome of Exorista sorbillans: the Tachinidae (Diptera: Calyptratae) perspective - Yuan-jun Shao; Xian-qiong Hu; Guang-da Peng; Rui-xian Wang; Rui-na Gao; Chao Lin; Wei-de Shen; Rui Li; Bing Li (Molecular Biology Reports, 2012)

Nucleotide sequence of a chickpea chlorotic stunt virus relative that infects pea and faba bean in China - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

Production of cloned transgenic cow expressing omega-3 fatty acids - Xia Wu; Hongsheng Ouyang; Biao Duan; Daxin Pang; Li Zhang; Ting Yuan; Lian Xue; Daibang Ni; Lei Cheng; Shuhua Dong; Zhuying Wei; Lin Li; et al. (Transgenic Research, 2012)

Differential DNA Methylation Status Between Human Preadipocytes and Mature Adipocytes - Jin-gai Zhu; Li Xia; Chen-bo Ji; Chun-mei Zhang; Guan-zhong Zhu; Chun-mei Shi; Lin Chen; Da-ni Qin; Xi-rong Guo (Cell Biochemistry and Biophysics, 2012)

Functional analysis of Waardenburg syndrome-associated PAX3 and SOX10 mutations: report of a dominant-negative SOX10 mutation in Waardenburg syndrome type II - Hua Zhang; Hongsheng Chen; Hunjin Luo; Jing An; Lin Sun; Lingyun Mei; Chufeng He; Lu Jiang; Wen Jiang; Kun Xia; Jia-Da Li; Yong Feng (Human Genetics, 2012)

Complete genomic sequence analysis reveals a novel fabavirus infecting cucurbits in China - Shu-Wei Dong; Hai-Ying Xiang; Qiao-Xia Shang; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

The cyclophosphamide metabolite, acrolein, induces cytoskeletal changes and oxidative stress in Sertoli cells - Feng Liu; Xu-Liang Li; Tao Lin; Da-Wei He; Guang-Hui Wei; Jun-Hong Liu; Lu-Sheng Li (Molecular Biology Reports, 2012)

Seasonal variation in population characteristics and management implications for brown rats (Rattus norvegicus) within their native range in Harbin, China - Da-Wei Wang; Lin Cong; Ling-Fen Yue; Bao-Huan Huang; Jian-Xu Zhang; Yu Wang; Ning Li; Xiao-Hui Liu (Journal of Pest Science, 2011)

Molecular characterization of two genotypes of a new polerovirus infecting brassicas in China - Hai-Ying Xiang; Shu-Wei Dong; Qiao-Xia Shang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2011)

Retinol, vitamins A, C, and E and breast cancer risk: a meta-analysis and meta-regression - Hu Fulan; Jiang Changxing; Wang Yi Baina; Zhang Wencui; Lin Chunqing; Wang Fan; Li Dandan; Sun Dianjun; Wang Tong; Pang Da; Zhao Yashuang (Cancer Causes & Control, 2011)

Characteristics of CO2 release from forest soil in the mountains near Beijing - Xiang Yang Sun; Cheng Da Gao; Lin Zhang; Su Yan Li; Yong Qiao (Environmental Monitoring and Assessment, 2011)

A novel strain of Beet western yellows virus infecting sugar beet with two distinct genotypes differing in the 5′-terminal half of genome - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Virus Genes, 2011)

Molecular characterization of two Chinese isolates of Beet western yellows virus infecting sugar beet - Hai-Ying Xiang; Shu-Wei Dong; Hui-Zhong Zhang; Wei-Lin Wang; Min-Quan Li; Cheng-Gui Han; Da-Wei Li; Jia-Lin Yu (Virus Genes, 2010)

Growth hormone and two forms of insulin-like growth factors I in the giant grouper (Epinephelus lanceolatus): molecular cloning and characterization of tissue distribution - Haiyan Dong; Lingxian Zeng; Da Duan; Haifa Zhang; Yunxin Wang; Wensheng Li; Haoran Lin (Fish Physiology and Biochemistry, 2010)

Evolution of the Chloroplast trnL-trnF Region in the Gymnosperm Lineages Taxaceae and Cephalotaxaceae - Da Cheng Hao; Bei Li Huang; Shi Lin Chen; Jun Mu (Biochemical Genetics, 2009)

Changes in estrogen receptor-α variant (ER-α36) expression during mouse ovary development and oocyte meiotic maturation - Bao-Zeng Xu; Sheng-Li Lin; Mo Li; Jia-Qiao Zhu; Sen Li; Ying-Chun Ouyang; Da-Yuan Chen; Qing-Yuan Sun (Histochemistry and Cell Biology, 2009)

Complete sequence analysis reveals two distinct poleroviruses infecting cucurbits in China - Hai-ying Xiang; Qiao-xia Shang; Cheng-gui Han; Da-wei Li; Jia-lin Yu (Archives of Virology, 2008)

Comparative Physicochemical Characterization of Phospholipids Complex of Puerarin Formulated by Conventional and Supercritical Methods - Ying Li; Da-Jian Yang; Shi-Lin Chen; Si-Bao Chen; Albert Sun-Chi Chan (Pharmaceutical Research, 2008)

Fibrarecisin, a novel triterpenoid from Fibraurea recisa with antitumor activity - Jiao-Long Fu; Chang-Heng Tan; Li-Ping Lin; Ji Huang; Da-Yuan Zhu (Natural Product Research, 2007)

Genotypic Analysis of Multidrug-Resistant Mycobacterium tuberculosis Isolates Recovered From Central China - Shu-Lin Zhang; Hua Qi; Dun-Lian Qiu; Da-Xu Li; Jie Zhang; Chang-Mei Du; Guo-Bin Wang; Zhi-Rong Yang; Qun Sun (Biochemical Genetics, 2007)

Apoptotic and anti-proliferative effects of 17β-estradiol and 17β-estradiol-like compounds in the Hep3B cell line - Erh-Jung Huang; Cheng-Chung Wu; Hsien-Ping Huang; Jer-Yuh Liu; Chung-Sheng Lin; Yan-Zin Chang; James A. Lin; Jaung-Geng Lin; Li-Mien Chen; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Over-expressed estrogen receptor-α up-regulates hTNF-α gene expression and down-regulates β-catenin signaling activity to induce the apoptosis and inhibit proliferation of LoVo colon cancer cells - Hsi-Hsien Hsu; Sue-Fei Cheng; Li-Mien Chen; Jer-Yu Liu; Chun-Hsien Chu; Yi-Jiun Weng; Zih-Ying Li; Chung-Sheng Lin; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Opposing Action of Estrogen Receptors α and β on Tumor Necrosis Factor-α Gene Expression and Caspase-8-mediated Apoptotic Effects in HA22T Cells - Erh-Jung Huang; Cheng-Chung Wu; Shin-Da Lee; Juen-Hau Chen; Jer-Yuh Liu; Jiunn-Liang Ko; James A. Lin; Min-Chi Lu; Li-Mien Chen; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2006)

Cardiomyoblast apoptosis induced by insulin-like growth factor (IGF)-I resistance is IGF-II dependent and synergistically enhanced by angiotensin II - Wei-Wen Kuo; Chung-Jung Liu; Li-Ming Chen; Chieh-Hsi Wu; Chun-Hsien Chu; Jer-Yuh Liu; Min-Chi Lu; James A. Lin; Shin-Da Lee; Chih-Yang Huang (Apoptosis, 2006)

Sequence Analysis of the Complete Genome of Rice Black-Streaked Dwarf Virus Isolated from Maize with Rough Dwarf Disease - Zhao-Hui Wang; Shou-Guo Fang; Jia-Ling Xu; Li-Ying Sun; Da-Wei Li; Jia-Lin Yu (Virus Genes, 2003)

Spatial-temporal variation of heavy metal elements content in covering soil of reclamation area in fushun coal mine - Jun-bao Yu; Jing-shuang Liu; Jin-da Wang; Zhong-gen Li; Xue-lin Zhang (Chinese Geographical Science, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)